USE AND POSITION OF THE PRONOUN SI WITH MODAL VERBS (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
In this paper we analyze the pronoun si that can be impersonal, reflexive and passive in the Italian language. With respect to the verb to which it is associated, the pronoun can change its place, especially in the presence of modal verbs. In the Romance languages, clitics derive from Latin and during their development they changed the position but also the functions. The clitic si, thus, may have different positions that we have tried to identify in the corpus formed of two writings, namely, Danubio and Pape Satàn Aleppe. The result of this analysis show that the authors apply typical rules in the case of impersonal and passivating pronoun, while we cannot say the same for the reflexive pronoun that is used in the enclitic position. In conclusion, by exploring our corpus we have created the space for further research on the pronoun si.
Keywords: Italian; impersonal si; reflexive si; passive si; modal verbs